EFFECTIVENESS OF HEALTH EDUCATION ON INFANT AND YOUNG CHILD FEEDING BEHAVIOR TO PREVENT STUNTING IN CHILDREN UNDER 2 YEARS: A SYSTEMATIC REVIEW - Syswianti, Desy; Mulyani , Sri; Pamungkasari , Eti Poncorini; Saptiwi, Betty (Malaysian Journal of Public Health Medicine, 2026)
Stunting in children under two years remains a critical global health challenge. While health education is a primary strategy, its effectiveness in reducing stunting—as opposed to merely changing behavior—remains debated. This systematic review aimed to evaluate the effectiveness of health education on Infant and Young Child Feeding (IYCF) behaviors and stunting prevention. Following PRISMA 2020 guidelines, a search was conducted in PubMed, Scopus, and ScienceDirect for studies published between 2014 and 2024. Inclusion criteria encompassed Randomized Controlled Trials (RCTs) and non-randomized studies evaluating maternal education. Risk of bias was assessed using Cochrane RoB 2 and JBI tools. Data synthesis was conducted using a narrative approach based on the Synthesis Without Meta-analysis (SWiM) framework. Nine studies met the inclusion criteria (six RCTs, three non-randomized). Narrative synthesis indicated that health education consistently improved Early Initiation of Breastfeeding, Exclusive Breastfeeding, and Dietary Diversity. Interventions combining interpersonal counseling with mass media or utilizing peer counselors demonstrated stronger behavioral impacts. However, the impact on linear growth (HAZ/stunting) was inconsistent. Improvements in nutritional status were more evident when education was integrated with health system strengthening or nutritional supplementation, rather than as a standalone intervention in food-insecure populations. Health education is effective in improving feeding behaviors but has variable capacity to reduce stunting if implemented alone. Behavioral improvements do not necessarily translate into child growth when structural barriers persist. Future policies should integrate education with nutrition-sensitive interventions, such as food security and sanitation, to achieve measurable impacts on child growth.